The American Broncho‐Esophagological Association Position Statement on Swallowing Fluoroscopy. (11th May 2022) - Dhar, Shumon Ian; Nativ‐Zeltzer, Nogah; Starmer, Heather; Morimoto, Linda Nayeli; Evangelista, Lisa; O'Rourke, Ashli; Fritz, Mark; Rameau, Anaïs; Randall, Derrick R.; Cates, Daniel; Allen, Jacqueline; Postma, Gregory; et al.
Abstract : Objectives: To develop an expert consensus statement on the clinical use of swallowing fluoroscopy in adults that reduces practice variation and identifies opportunities for quality improvement in the care of patients suffering from swallowing impairment. Methodology: A search strategist reviewed data sources (PubMed, Embase, Cochrane, Web of Science, Scopus) to use as evidence for an expert development group to compose statements focusing on areas of controversy regarding swallowing fluoroscopy. Candidate statements underwent two iterations of a modified Delphi protocol to reach consensus. Results: A total of 2184 publications were identified for title and abstract review with 211 publications meeting the criteria for full text review. Of these, 148 articles were included for review. An additional 116 publications were also included after reviewing the references of the full text publications from the initial search. These 264 references guided the authors to develop 41 candidate statements in various categories. Forty statements encompassing patient selection, fluoroscopic study choice, radiation safety, clinical team dynamics, training requirements, videofluoroscopic swallow study and esophagram techniques, and interpretation of swallowing fluoroscopy met criteria for consensus. One statement on esophagram technique reached near‐consensus. Conclusions: These 40 statements pertaining to the comprehensive use of swallowing fluoroscopy in adults can guide the development of best practices, improve quality and safety of care, and influence policy in both the outpatient and inpatient settings. The lack of consensus on some aspects of esophagram technique likely reflects gaps in knowledge and clinical practice variation and should be a target for future research. Laryngoscope, 133:255–268, 2023